Gut Microbial Dysbiosis and Cognitive Impairment in Bipolar Disorder: Current Evidence - Dai, Wenyu; Liu, Jieyu; Qiu, Yan; Teng, Ziwei; Li, Sujuan; Yuan, Hui; Huang, Jing; Xiang, Hui; Tang, Hui; Wang, Bolun; Chen, Jindong; Wu, Haishan (Frontiers in Pharmacology, 2022)
Recent studies have reported that the gut microbiota influences mood and cognitive function through the gut-brain axis, which is involved in the pathophysiology of neurocognitive and mental disorders, including Parkinson’s disease, Alzheimer’s disease, and schizophrenia. These disorders have similar pathophysiology to that of cognitive dysfunction in bipolar disorder (BD), including neuroinflammation and dysregulation of various neurotransmitters (i.e., serotonin and dopamine). There is also emerging evidence of alterations in the gut microbial composition of patients with BD, suggesting that gut microbial dysbiosis contributes to disease progression and cognitive impairment in BD. Therefore, microbiota-centered treatment might be an effective adjuvant therapy for BD-related cognitive impairment. Given that studies focusing on connections between the gut microbiota and BD-related cognitive impairment are lagging behind those on other neurocognitive disorders, this review sought to explore the potential mechanisms of how gut microbial dysbiosis affects cognitive function in BD and identify potential microbiota-centered treatment.